Implementation of Sustainable Tourism Principles in Sport Tourism: Sustainability Efforts by Pocari Run Organizers - Sugiri, Rashid Algani; Lemy, Diena M. (Institut Pariwisata dan Bisnis Internasional, 2023)
Sustainable tourism has become part of the general desire of Indonesia’s tourism development. The industry continuously seek ways or avenues where sustainable tourism practices can be adopted in hopes to achieve the desired outcomes of sustainable tourism. One of the ways of looking for new avenues that can adopt sustainable practices is to look at the emerging sectors of tourism. An interesting lane of tourism that can do this is sports tourism. Sports tourism relationship with sustainable tourism has been studied prior with promising potential. This study explores the sustainability efforts around marathon events by the organizers added with the participants point of view. For the research, this study will take the case study format focusing on Pocari Run. It puts forward the question whether event organizers are willing to implement sustainable tourism practices in their events and are aware sustainable tourism practices can be used as a tool for marathon events success and how it is impacting the participants. The methodology used in this research is a qualitative method, extracting insights from informants through in-depth interview directed towards Pocari Run Organizers. This study has found that the implementation of sustainable tourism practices have been implemented in Pocari Run events in accordance to previous studies. The implementation itself proved to be valuable in helping organizers develop a positive relationship with local stakeholders such as the local community and local government.